Documenting acousmatic music interpretation: Profiles of discourse across multiple dimensions. Issue 1 (28th August 2018) - Boutard, Guillaume; Féron, François-Xavier
Abstract : Purpose: Extending documentation and analysis frameworks for acousmatic music to performance/interpretation, from an information science point of view, will benefit the transmission and preservation of a repertoire with an idiosyncratic relation to performance and technology. The purpose of this paper is to present the outcome of a qualitative research aiming at providing a conceptual model theorizing the intricate relationships between the multiple dimensions of acousmatic music interpretation. Design/methodology/approach: The methodology relies on the grounded theory. A total of 12 Interviews were conducted over a period of three years in France, Québec and Belgium, grounded in theoretical sampling. Findings: The analysis outcome describes eight dimensions in acousmatic performance, namely, musical, technical, anthropological, psychological, social, cultural, linguistic and ontological. Discourse profiles are provided in relation to each participant. Theory development led to the distinction between documentation of interpretation as an expertise and as a profession. Research limitations/implications: Data collection is limited to French-speaking experts, for historical and methodological reasons. Practical implications: The model stemming from the analysis provides a framework for documentation which will benefit practitioners and organizations dedicated to the dissemination of acousmatic music. The model also provides this community with a tool for characterizing expert discourses about acousmatic performance and identifying content areas to further investigate. From a research point of view, the theorization leads to the specification of new directions and the identification of relevant epistemological frameworks. Originality/value: This research brings a new vision of acousmatic interpretation, extending the literature on this repertoire's performance with a more holistic perspective.